DABCO-catalyzed synthesis of 3-substituted-3-hydroxyindolin-2-ones in aqueous media. Issue 7 (2nd April 2016) - Tiwari, Keshri Nath; Bora, Darshana; Chauhan, Garima; Yadav, Deepika; Sharma, Kavita; Thakur, Ashima; Singh, Lachhman; Tripathi, Vishwadeep
ABSTRACT: An efficient and greener protocol for easy access to 3-susbstituted-3-hydroxy-2-oxindoles by the reaction with various substituted isatins and acetophenones is described. This protocol is widely applicable for a variety of isatins and acetophenones using water as a reaction media and 1, 4-diazabicyclo[2.2.2]octane (DABCO) as catalyst with shorter reaction time and good to excellent yield of products. GRAPHICAL ABSTRACT: